Comprehensive Energy Performance Assessment of a Lecturer Building in a Malaysian Public University - Norfakhira Mohd Nor; Razali, Mohd Azahari; Nur Syafiqah Adha Narrudin; Nur Adlin Abu Bakar; Siti Birkha Mohd Ali; Nur Erma Nardiah Nazami; Masataro Suzuki (International Journal of Integrated Engineering, 2026)
The increasing energy consumption of public university buildings in Malaysia has raised concern, particularly regarding the energy performance of lecturer rooms which is a topic often overlooked in broader campus-level studies. This research addresses that gap by analysing the energy usage patterns of the C16 lecturer building at Universiti Tun Hussein Onn Malaysia (UTHM). Previous studies have lacked continuous monitoring and system-level differentiation, limiting insights into specific energy demands. In contrast, this study uses detailed energy audits, data logging, and visual inspections to assess lighting and air-conditioning performance based on Malaysian Standard MS1525. Findings reveal that air-conditioning dominates energy use, accounting for 94% of total consumption, while lighting contributes only 6%. Usage patterns align with occupancy and time of day, and several areas exhibit deviations from recommended lighting and HVAC conditions. These results highlight key opportunities for energy conservation measures such as HVAC system optimization, lighting controls, and improved insulation. The study provides practical guidance for improving energy efficiency in academic buildings and underscores the importance of room-level profiling in tropical climates.